Geniposide reduces cholesterol accumulation and increases its excretion by regulating the FXR-mediated liver-gut crosstalk of bile acids. (February 2020) - Liu, Jinxin; Li, Yan; Sun, Chao; Liu, Shengnan; Yan, Ying; Pan, Haiou; Fan, Mingcong; Xue, Lamei; Nie, Chenzhipeng; Zhang, Hui; Qian, Haifeng; Ying, Hao; et al.
Graphical abstract: Highlights: Geniposide improves cholesterol homeostasis. Geniposide deactivates the negative feedback regulation of bile acids. Geniposide regulates liver-gut crosstalk of bile acids. FXR suppression plays an important regulatory role of geniposide function. Abstract: Hypercholesterolemia is the main risk factor to threaten human health and geniposide has been found to have hypolipidemic functions. However, its underlying mechanism is not clear. In this study, we firstly confirmed the hypolipidemic functions of geniposide in C57BL/6 and ApoE −/− mice (i.p, 50 mg/kg/d). Then hepatic or arterial lipid accumulation was analyzed through histomorphology. Moreover, the effects of geniposide on the bile acid metabolism were analyzed by the hepatic RNA-seq and biological molecular analysis. Mechanistically, GW4064, an FXR agonist, was carried out to verify the mechanisms of geniposide in human HepG2 and Caco2 cells. As expected, geniposide decreased the lipid accumulations both in plasma and liver. Morever, the atherosclerotic plaque shrank in HCD-fed ApoE −/− mice with geniposide treatment. The molecular analysis revealed that geniposide accelerated the hepatic synthesis of bile acids through inactivating the negative feedback regulation of bile acids mediated by FXR, led to the enhancive reverse cholesterol transport and cholesterol catabolism. What's more, geniposide reduced ileal FXR-mediated reabsorption of bile acids, resulting in the increasing excretion of bile acids. Our study pointed out the regulatory functions of geniposide on FXR-mediated liver-gut crosstalk of bile acids and geniposide might be a novel strategy for maintaining cholesterol homeostasis.